Therapeutic and safety considerations of nanoparticle-mediated drug delivery in pregnancy. (July 2015) - Keelan, Jeffrey A; Leong, Joan W; Ho, Diwei; Iyer, K Swaminatha
Advances in nanotechnology have resulted in the design of effective, safe and tissue-selective nanocarriers for delivering therapeutics to treat malignancies, infections and other diseases. In pregnancy, nanoparticle-based drug formulations could have the potential to selectively target either the placenta and/or fetus, enabling 'fetal-friendly' drugs to be administered in pregnancy with minimal risk of off-target effects. A considerable amount of research has been carried out on maternal-placental-fetal nanoparticle uptake, transfer and toxicity using rodent and ex vivo models. However, the development of placental targeting strategies and the therapeutic evaluation of nanoformulations in pregnancy remains in its infancy. While some promising avenues are currently under investigation, much work is needed to bring the advantages of nanoparticle-based drug therapy in pregnancy to clinical reality.